Mucosal Immunization of Cynomolgus Macaques with Two Serotypes of Live Poliovirus Vectors Expressing Simian Immunodeficiency Virus Antigens: Stimulation of Humoral, Mucosal, and Cellular Immunity - Crotty, Shane (American Society for Microbiology, 1999)
Poliovirus live virus vectors are a candidate recombinant vaccine system. Previous studies using this system showed that a live poliovirus vector expressing a foreign antigen between the structural and nonstructural proteins generates both antibody and cytotoxic T-lymphocyte responses in mice. Here we describe a novel in vitro method of cloning recombinant polioviruses involving a hybrid-PCR approach. We report the construction of recombinant vectors of two different serotypes of poliovirus-expressing simian immunodeficiency virus (SIV) antigens and the intranasal and intravenous inoculations of four adult cynomolgus macaques with these poliovirus vectors expressing the SIV proteins p17(gag) and gp41(env). All macaques generated a mucosal anti-SIV immunoglobulin A (IgA) response in rectal secretions. Two of the four macaques generated mucosal antibody responses detectable in vaginal lavages. Strong serum IgG responses lasting for at least 1 year were detected in two of the four monkeys. SIV-specific T-cell lymphoproliferative responses were detected in three of the four monkeys. SIV-specific cytotoxic T lymphocytes were detected in two of the four monkeys. This is the first report of poliovirus-elicited vaginal IgA or cytotoxic T lymphocytes in any naturally infectable primate, including humans. These findings support the concept that a live poliovirus vector is a potentially useful delivery system that elicits humoral, mucosal, and cellular immune responses against exogenous antigens.